2020
DOI: 10.1101/2020.12.12.422516
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 RNA reverse-transcribed and integrated into the human genome

Abstract: SummaryProlonged SARS-CoV-2 RNA shedding and recurrence of PCR-positive tests have been widely reported in patients after recovery, yet these patients most commonly are non-infectious1–14. Here we investigated the possibility that SARS-CoV-2 RNAs can be reverse-transcribed and integrated into the human genome and that transcription of the integrated sequences might account for PCR-positive tests. In support of this hypothesis, we found chimeric transcripts consisting of viral fused to cellular sequences in pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 49 publications
4
39
1
5
Order By: Relevance
“…We next quantified the reads that partly mapped to the human genome and partly mapped to the SARS-CoV2 genome (see methods ). We found that nearly 0.05-1% of all viral reads are formed of hybrid sequences between host and virus RNAs, a frequency consistent with that recently reported by others 15,16 ( Fig. 1C ).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We next quantified the reads that partly mapped to the human genome and partly mapped to the SARS-CoV2 genome (see methods ). We found that nearly 0.05-1% of all viral reads are formed of hybrid sequences between host and virus RNAs, a frequency consistent with that recently reported by others 15,16 ( Fig. 1C ).…”
Section: Resultssupporting
confidence: 91%
“…RNA-sequencing reads that partly align to the host genome and partly align to the viral genome are the signature of HVC events in RNA-sequencing datasets. Recent reports 15,16 suggesting the presence of HVC events in SARS-CoV2-infected cells have been interpreted as supporting viral integration into the human genome as a mechanism of viral persistence. To gain insights into the authenticity of these events, we re-analyzed the 3 available RNA-seq datasets from patients with COVID-19 (n=57 samples) and in vitro SARS-CoV2 infected cells (n=64 samples).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Рекомбинация мРНК ретротранспозонов и РНК экзогенного неретровируса приводит к интеграции комплементарной к ней ДНК в геном [23], поэтому включение информации о mРНКвакцине в геном прививаемого не представляется невозможным. Применительно к SARS-Cov-2 в условиях in vitro уже подтверждено включение его генома в геном человека [30].…”
Section: векторные вакцины или мрнк-вакцины?unclassified
“…It is already clear, though mobile and exchangeable, that the human microbiome is part of our functional body (Ogunrinola et al 2020) and that a change in the microbiome, as well as viral gene transfer, is transformative to the body. At the time of writing there exists only a preprint of a yet-to-be-peer-reviewed paper about SARS-CoV-2 RNA fragments in the human genome (Zhang et al 2020) and little can be said about any consequences. However, it points towards the possibility of a deep future of the virus as part of the human genome.…”
Section: An Overviewmentioning
confidence: 99%